Pengaruh Literasi Keuangan dan Inklusi Keuangan Terhadap Kinerja UMKM Di Kecamatan Kadipaten - R. Neny Kusumadewi; Haris Fauzi; Alan Rusdiana; Muhammad Mahfudin Fasha (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2026)
Understanding and knowledge about how to manage finances in a business is very important for all business actors, currently many MSMEs in Kadipeten District are still hampered in their development due to various things, one of which is the understanding of financial literacy and financial inclusion in maximizing the performance of their MSMEs is still not optimal. So this study has the aim to calculate the Effect of Financial Literacy and Financial Inclusion on MSME Performance (Case Study on MSMEs in Kadipaten District). The method in this research is a quantitative method using descriptive and verification analysis. Then 100 respondents who are MSME actors in Kadipaten District are the population in this study. The sampling technique uses Nonprobability sampling with Incidental sampling. The data collection technique is a questionnaire using a Likert scale. Data analysis uses classical assumption tests, multiple linear regression analysis, coefficient of determination, model feasibility tests and partial hypothesis tests. The results of the study indicate that Financial Literacy has a positive and significant effect on MSME Performance and Financial Inclusion has a positive and significant effect on MSME Performance.